Validade concorrente entre os dinamômetros isocinéticos Biodex e Kineo em atletas de futebol - Pereira, Albino Luciano Abreu (2024)
Football is a sport of great global economic importance. Injuries in professional athletes can cause significant financial losses due to the interruption of training and games. Clubs invest in tools to monitor athletes and manage injury risk, as these are influenced by biomechanical, psychological, physiological, and contextual factors. Muscle strength, a modifiable factor, is crucial in identifying asymmetries indicative of risks. Isokinetic dynamometry, especially with Biodex equipment, is considered one of the best ways to assess muscle performance. However, equipment like the Kineo Training System (Kineo) is being adopted, although more studies are needed to validate its properties. Objective: to analyze the concurrent validity between the isokinetic dynamometer Biodex and the Kineo in football athletes. Methods: this is a validation study with a cross-sectional design conducted at the Movement Analysis Laboratory in partnership with the physiotherapy department of a first-division Brazilian football club, with data collection from July to November 2023. Athletes over 18 years old from the professional men's and women's teams were evaluated. The athletes performed an assessment on each equipment, with 5 repetitions at 60°/s, analyzing peak torque (Biodex), force (Kineo), total work, momentum (Kineo), and the hamstring/quadriceps ratio on both devices. Results: a total of 55 athletes participated, 40% women (22) and 60% men (33). The Kineo presented a Spearman correlation coefficient (rho) ranging from 0.31 to 0.67 in the evaluation of the peak torque of the Biodex with the force of the Kineo, indicating a weak correlation for both absolute values and values normalized by body weight. Correlating the peak torque of the Biodex with the momentum of the Kineo, the values ranged from 0.41 to 0.70, demonstrating a weak to reasonable correlation, similar to the work relationship (extensors 0.66 and flexors 0.70). The hamstring/quadriceps ratio showed a rho of 0.20, indicating a weak correlation. Conclusion: the results indicate that it is not possible to estimate an athlete's performance on the Biodex from the Kineo results due to the weak correlation between the equipment.